Inventarisasi Keanekaragaman Anggrek (Orchidaceae) di Kecamatan Polinggona Kabupaten Kolaka - Selamet Kurniawan Riandinata; Athifah Athifah; Muh. Ramdhan Sofyan Syafii (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Orchid is type of flowering plant that has economic value because most of them have beautiful and attractive flowers. The existence species of orchids in nature is increasingly threatened due to the high activity of land conversion and hunting for the orchids themselves. The purpose of this study was determine the diversity of orchids spesies in Polinggona, Kolaka district Southeast Sulawesi. The research used an explorative and interview method. Based on the observations, there were 31 species of epiphytic orchids, 5 species of terrestrial orchids, one semi-terrestrial orchid and there are 6 species of orchids is unidentified.The results of vertical distribution on the host tree, the epiphytic orchids found growing in all zones were Pomatocalpa spicata and Dendrobium ephemerum and mostly the epiphytic orchids in the observation site grew in zone III, specifically at the base of branching of its host tree.Terrestrial orchid type Arundina graminifolia has the most limited distribution compared to other terrestrial orchid species. The types of terrestrial and semi-terrestrial orchids that were found were all close to the river flow.